OF ORGANIC SUBSTANCES BY THIN LAYER CHROMATOGRAPHIC METHOD - Toshboyev Feruz Nizomiddinovich; Izatullayev Sarvar Abdimannonovich; Akhmadov Javokhir Zoirovich (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: An important advantage of chromatographic methods is speed, i.e. express method. In chemical analysis, there are more types of surface chromatography performed on paper or a thin layer of sorbent. Thin layer chromatography - substances in the mixture are separated due to the different distribution of the mobile eluent (mixture of solvents) and the thin layer of the sorbent uniformly attached to the plate [2,3,7]. To perform chromatography on a thin layer of a sorbent, a sorbent-plaster mixture is evenly spread on the surface of a glass or foil plate using a special device and dried. A starting line is drawn with a soft pencil at a distance of 1.5 cm from the bottom edge of the plate . A small drop of the test solution and the standard solution of the substance to be detected is dropped in a thin capillary device at a distance of 1.0-1.5 cm from the start line. At the bottom of the plate, a glass (column) with a 1 cm thick eluent is placed vertically, and the mouth of the glass is closed[4,6,8]. The eluent moistens the sorbent and moves to the finish line by dissolving the substances brought to the starting-line.